2015
DOI: 10.1158/1538-7445.am2015-2488
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2488: FGFR4 as a potential therapeutic target for monoclonal antibody based intervention in rhabdomyosarcoma

Abstract: Background: Rhabdomyosarcoma (RMS) is most common soft tissue sarcoma in childhood and adolescence. There are two major subtypes of RMS - alveolar RMS (ARMS) and embryonal RMS (ERMS). With current treatment modalities the 5 year survival rate of patients with metastatic disease is only about 30%, thus necessitating development of novel targeted therapeutic strategies. Fibroblast Growth Factor Receptor 4 (FGFR4) is highly differentially expressed gene and activating mutations in FGFR4 is associated with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, we could achieve effective cell-mediated cytotoxicity with FGFR4-CAR T cells in vitro. Therapies for RMS based on FGFR4 antibodies have been investigated pre-clinically with promising results, either as antibody–drug conjugates (ADC) [ 56 , 57 , 58 ], or with the antigen-binding domain grafted on chimeric antigen receptors (CARs) to generate CAR T cells [ 59 ]. With our work, we show here a novel FGFR4-targeting based on sdAb by active drug delivery and T cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we could achieve effective cell-mediated cytotoxicity with FGFR4-CAR T cells in vitro. Therapies for RMS based on FGFR4 antibodies have been investigated pre-clinically with promising results, either as antibody–drug conjugates (ADC) [ 56 , 57 , 58 ], or with the antigen-binding domain grafted on chimeric antigen receptors (CARs) to generate CAR T cells [ 59 ]. With our work, we show here a novel FGFR4-targeting based on sdAb by active drug delivery and T cell recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of microarrays, and later of next-generation RNA sequencing led to the identification of several genes coding for surface proteins highly expressed in RMS tumors, FGFR4 being the most prominent [37][38][39]. Monoclonal antibodies [40], ADC [41], and CAR T cells are being developed with promising preclinical results [42,43]. Gene expression profiling has revealed that the gene coding for the cannabinoid receptor 1 (CB1) is highly upregulated in FP-RMS [44], but no targeting approaches have been developed yet.…”
Section: Introductionmentioning
confidence: 99%